Изучение социальных конфликтов в немецкой социологии: классические и современные ориентиры - Майструк, Н. (Социология: теория, методы, маркетинг, 2004)
Various concept approaches make it possible to understand the globalization as transformation of the everyday personal life structures. The special attention is paid to the cultural aspect of globalization processes that bring not only the positives but a real danger when countries and persons can lose their cultural characteristic features. In The one-polar world, the most intensive globalization processes take place in the mass information field, the Internet becomes more significant. It has created a new kind of communication. It affects communicating participants, changes the social and cultural space of personal life. The article is about the involvement of Ukrainian people into the world informational net. The effect of the Internet on user's personality has been assessed by various age, ethnic, ethno-linguistic and other groups of Ukrainian population.